Pengaruh Model Pembelajaran Collaborative Problem Solving terhadap Kemampuan Pemecahan Masalah Matematis ditinjau dari Minat Belajar - Jumala, Nila; Fitri, Amalia (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
The purpose of this study was to: (1) determine whether students who use the Collaborative Problem Solving learning model and students who use the conventional learning model have different abilities in solving mathematical problems; (2) determine whether students with high, medium, and low learning interests have different abilities in solving mathematical problems; and (3) determine whether the Collaborative Problem Solving model and learning interests have an interaction on students' mathematical problem solving abilities. The study employs a quantitative approach using a posttest-only control group design, which is a quasi-experimental design. All grade XI students of SMA Negeri 1 Ulujami made up the research population. Data collection was carried out through tests and questionnaires. The research instruments were descriptive questions that measured mathematical problem solving ability and questionnaires to assess students' learning interests. The two-way analysis of variance (two-way ANOVA) method was used to evaluate the hypotheses. According to the study's findings, it was discovered that: (1) students who received the Collaborative Problem Solving learning model performed differently in solving mathematical problems than students who received the conventional learning model; (2) students with high, medium, or low learning interest performed differently in solving mathematical problems; and (3) there was no interaction between the Collaborative Problem Solving model and learning interest.